A survey on the development of Islamic higher education in Indonesia: an epistemological review - Sa'adi Sa'adi (Indonesian Journal of Islam and Muslim Societies, 2011)
Social changes, development and advancement of humans’ culture influence education as inseparable aspect of human life. In line with Islamic higher education many thinkers proposed their ideas of how to formulate its appropriate epistemological background in different views. There are some notable persons for this field, such as Iqbal, Fazlur Rahman, Afzalur Rahman, Al-Faruqi which to some extent parallel or influence Indonesian thinkers’ such as Mukti Ali, Harun Nasution, Cak Nur, Amin Abdullah, etc. Some are still at the level of speculative thought, while others have applied their ideas in educational institutions, like Amin Abdullah and Imam Suprayoga. Perubahan sosial, perkembangan dan kemajuan kebudayaan umat manusia memengaruhi pendidikan yang merupakan bidang yang tak terpisahkan dari kehidupan manusia itu sendiri. Dalam hal pendidikan tinggi Islam, para pemikir mengajukan berbagai gagasan mereka tentang bagaimana merumuskan dasardasar epistemologinya yang paling tepat. Ada beberapa tokoh pemikir penting yang perlu dicatat (dari luar negeri) dalam hal ini seperti Iqbal, Fazlur Rahman, Afzalur Rahman, al-Faruqi, yang dalam batas tertentu secara paralel atau memengaruhi para pemikir Indonesia seperti Mukti Ali, Harun Nasution, Cak Nur, Amin Abdullah dan Imam Suprayoga. Sebagian dari pemikir tersebut masih pada dataran pemikiran spekulatif, sementara yang lain sudah mengaktualisasikannya dalam implementasi kelembagaan pendidikan tinggi Islam, seperti Amin Abdullah dan Imam Suprayoga.